Penerapan Scientific Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas 2 SD Bab “Keluargaku Unik” - Indiana Zulfia Malik; Puji Rahayu; Tri Eko Baktiono (Jurnal Pendidikan Dirgantara, 2025)
This study aimed to improve the learning outcomes of second-grade students at SD Negeri Latsari Tuban in Indonesian language lessons, specifically focusing on the theme "My Unique Family." The classroom activities were designed to encourage active student participation through group discussions on related topics. The research was conducted over two cycles, applying a scientific approach to the learning process.The findings showed a 20% improvement in student learning outcomes, with the average score increasing to 8.68. Mastery levels also improved significantly, from 69% in the first cycle to 89% in the second cycle. These results demonstrate that the scientific approach effectively enhanced student understanding and engagement during the lessons.Overall, the study concludes that the scientific approach is a beneficial method for improving learning outcomes in Indonesian language subjects. It also suggests the broader applicability of this method for enhancing student achievement across other themes and subject areas.